Association between herpes simplex virus infection and Alzheimer’s disease biomarkers: analysis within the MAPT trial - Morgane Linard; Isabelle Garrigue; Bruno Vellas; Nicola Coley; Henrik Zetterberg; Kaj Blennow; Nicholas James Ashton; Pierre Payoux; Anne-Sophie Salabert; Jean-François Dartigues; Joachim Mazere; Sandrine Andrieu; et al. (Scientific Reports)
Abstract In vitro and animal studies have suggested that inoculation with herpes simplex virus 1 (HSV-1) can lead to amyloid deposits, hyperphosphorylation of tau, and/or neuronal loss. Here, we studied the association between HSV-1 and Alzheimer’s disease biomarkers in humans. Our sample included 182 participants at risk of cognitive decline from the Multidomain Alzheimer Preventive Trial who had HSV-1 plasma serology and an amyloid PET scan. Plasma Aβ42/40 ratio, neurofilament light chain and p-tau181 were also available for a sub-sample of participants. Multivariate linear regressions were performed and stratified by APOE4 genotype. The median age was 74.0 years, 85.2% were infected with HSV-1. Infected participants tended to have a lower cortical amyloid load than uninfected participants (β = -0.08, p = 0.06), especially those suspected of reactivating HSV-1 most frequently (i.e. with a high anti-HSV-1 IgG level; n = 58, β = -0.09 p = 0.04). After stratification, the association was only significant in APOE4 carriers (n = 43, β = -0.21 p = 0.01). No association was found with the plasma biomarkers. The trend toward lower cortical amyloid load in HSV-1-infected participants was unexpected given the pre-existing literature and may be explained either by a modified immune response in HSV-1 infected subjects which could favour the clearance of amyloid deposits or by a selection bias.